Efektifitas Kinerja Perangkat Desa Dalam Melayani Masyarakat Berdasarkan UU No. 23 Tahun 2014 - Sondang Ruth Lovenia Sinaga; Farhan Azra Hasibuan; Ira Yenita Malau; Tegar Haykal Parapat; Lastri Siregar; Sri Hadiningrum (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
This research is motivated by the fact that public services provided by government officials often tend to be complicated, such as: Service procedures, low level of education of officials, work discipline. This greatly influences the quality of public services in village government. This research has the main objective of establishing the government, namely to maintain a peaceful system in which society can live a normal life and improve the welfare of its people. In other words, in essence it is service to the community which is the main function of the government and is the government's obligation in managing its government, both central, regional and especially village governments which have direct contact with the community. This research using normative juridical research methods, normative juridical, namely legal research carried out by examining library materials or secondary data. The research results concluded that the effectiveness of village officials' performance in serving the community is very important in the context of implementing Law no. 23 of 2014. The success of village officials in understanding and implementing it has a direct impact on the welfare of the community at the local level. Therefore, it is necessary to continue to improve the quality of human resources, facilities and infrastructure at the village level to ensure optimal services in accordance with the provisions of the Law.